2022
DOI: 10.1002/cctc.202200312
|View full text |Cite
|
Sign up to set email alerts
|

Piezodeposition of Metal Cocatalysts for Promoted Piezocatalytic Generation of Reactive Oxygen Species and Hydrogen in Water

Abstract: Piezocatalysis in aqueous medium has shown great potential for various applications, however the efficiency of piezocatalytic nanoparticles is harmed by the limited utilization of piezoelectric charge and the lack of active catalytic interface. In this study, BaTiO3@Metal (BTO@M, M=Pt, Pd and Au) hetero‐nanostructures were synthesized by using a piezodeposition method. The deposited metal cocatalysts significantly promote the separation and migration of piezogenerated charge, consequently enhancing the piezoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…28−30 In our previous study, BTO@Au exhibited the most efficient generation of reactive oxidative species under ultrasonic vibrations when compared to BTO@Pt and BTO@Pd. 31 Therefore, BTO NPs with a diameter of about 200 nm were embedded into the PCL surface by a simple polymer casting method, and then the BTO NPs were decorated with Au cocatalysts by an in situ piezo-deposition process to finally obtain the piezoPCL film (Figure 1a). The pristine crystalline BTO NPs possess typical perovskite phase structure (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28−30 In our previous study, BTO@Au exhibited the most efficient generation of reactive oxidative species under ultrasonic vibrations when compared to BTO@Pt and BTO@Pd. 31 Therefore, BTO NPs with a diameter of about 200 nm were embedded into the PCL surface by a simple polymer casting method, and then the BTO NPs were decorated with Au cocatalysts by an in situ piezo-deposition process to finally obtain the piezoPCL film (Figure 1a). The pristine crystalline BTO NPs possess typical perovskite phase structure (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Under mechanical stimulation, piezoelectric electrons generated from the stressed BTO NPs can be transferred to the deposited Au cocatalysts with a high work function, leading to efficient charge separation. With the aid of Au cocatalysts, the discharged electrons will then react with H 2 O and dissolved O 2 in surrounding medium to produce superoxide anions (•O 2 − ), hydroxyl radicals (•OH), and other ROS species 31 (Figure 2a). Total ROS production of PCL and piezoPCL(x) samples were detected, as shown in Figure 2b, and with the increase of the BTO NP loading, the ROS generation capacity was gradually enhanced with the increase of the ultrasonic irradiation time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that •OH, •O 2− , and 1 O 2 were the main oxidative species produced by piezocatalysis from piezoTi, which was similar to other BTO-based piezocatalysis. [16,27,28] The oxidative radicals were also identified by the electron spin resonance (ESR) spectra (Figure S9, Supporting Information). The promoted ROS generation ability of piezoTi was ascribed to the efficient charge separation on the piezotronic surface and Au cocatalyst-assisted oxygen reduction reactions [28] (Figure 2i), which suggested potential piezodynamic therapy capability.…”
Section: Piezoelectric Properties and Ros Generation Efficiencymentioning
confidence: 99%
“…This media is generally considered to be water which is abundant in all cell tissues. 97 In the presence of ultrasound, there develops a large number of vapour-filled bubbles which experience a quasiadiabatic collapse and create an elevated pressurized atmosphere. 98,99 Elimination of system pressure results in molecular deformation or structural distortion, which can be a reason for the implementation of a local dipole moment.…”
Section: Role Of Ultrasound For Ros Generationmentioning
confidence: 99%